Bayesian epidemic models for spatially aggregated count data. (12th June 2017) - Malesios, Chrisovalantis; Demiris, Nikolaos; Kalogeropoulos, Konstantinos; Ntzoufras, Ioannis
Abstract : Epidemic data often possess certain characteristics, such as the presence of many zeros, the spatial nature of the disease spread mechanism, environmental noise, serial correlation and dependence on time‐varying factors. This paper addresses these issues via suitable Bayesian modelling. In doing so, we utilize a general class of stochastic regression models appropriate for spatio‐temporal count data with an excess number of zeros. The developed regression framework does incorporate serial correlation and time‐varying covariates through an Ornstein–Uhlenbeck process formulation. In addition, we explore the effect of different priors, including default options and variations of mixtures of g ‐priors. The effect of different distance kernels for the epidemic model component is investigated. We proceed by developing branching process‐based methods for testing scenarios for disease control, thus linking traditional epidemiological models with stochastic epidemic processes, useful in policy‐focused decision making. The approach is illustrated with an application to a sheep pox dataset from the Evros region, Greece. Copyright © 2017 John Wiley & Sons, Ltd.